DISSOLUTION ENHANCEMENT OF POORLY WATER-SOLUBLE DRUG BY CYCLODEXTRINS INCLUSION COMPLEXATION - Mendhe, A. A.; Kharwade, R. S.; Mahajan, U. N. (International Journal of Applied Pharmaceutics, 2016)
Objective: Solubility of a drug is an important property that mainly influences the extent of oral bioavailability. Enhancement of oral bioavailability of poorly water-soluble drugs is the most challenging aspects of drug development. It is very important to find appropriate formulation approaches to improve the aqueous solubility and bioavailability of poorly aqueous soluble drugs. Ezetimibe is a new lipid lowering agent in the management of hypercholesterolemia. The drug is water-insoluble, lipophilic, and highly permeable according to the pharmaceutical classification system. Therefore, the bioavailability of ezetimibe may be improved by increasing its solubility. Methods: In present work solubility of ezetimibe was increased with inclusion complexes by a different technique like physical mixture, co-grinding and modified kneading method. The physical properties of the prepared inclusion complex of ezetimibe were characterised by Differential scanning calorimetry (DSC), X-ray diffraction spectroscopy (XRD), Fourier transform infra-red spectroscopy (FTIR) and in vitro dissolution studies. Results: From the dissolution studies of ezetimibe with HP-Î²-cyclodextrin(1:1 and 1:2), we conclude that the prepared complexes of ezetimibe with HP-Î²-cyclodextrin (1:2) by modified kneading method showed higher release i.e. 88.35% in 60 min. than in (1:1) 76.75% in 60 min. So, ezetimibe with HP-Î²-cyclodextrin (1:2) inclusion complex was used to formulate tablet by direct compression method. Conclusion: From the dissolution data of formulated tablets was observed that drug release was more in tablet dosage form as compared to plain ezetimibe and especially formulation in a ratio of 1:2 was found the promising result. Also from one-month stability data shows no significant change compared to the initial result.